Korelasi Pola Asuh Orang Tua Terhadap Kemandirian Pemilihan Karir pada Siswa Kelas X SMK Muhammadiyah 3 Weleri - Mundrikah, Umi; Handayani, Arri; Lestari, Farikha (Melati Institute, 2024)
The Correlation of Parenting Patterns to the Independence of Career Selection of Class X Students of SMK Muhammadiyah 3 Weleri is motivated by students making career plans based only on their will and desire without considering their abilities. Student career selection is not just a job that is chosen, but a job that is truly in accordance with their potential, so in this case parenting patterns from parents are intended to provide motivation and support to students in choosing their careers. The formulation of the problem in this study is how is the correlation between parenting patterns and career choices of class X students of SMK Muhammadiyah 3 Weleri. This type of research is quantitative research with correlational research design. The population in this study were all students of class X SMK Muhammadiyah 3 Weleri. The sampling technique in this study is simple random sampling obtained from a questionnaire of parental parenting and career choice independence. The results of this study indicate that the results of the correlation test, obtained that the sig.(2-tailed) value on the parental parenting variable is 0.463 and the sig. (2-tailed) value of career selection is 0.463. In this hypothesis test analysis, it can be concluded that the sig.(2-tailed) value of parental parenting and career selection is 0.463>0.05, so there is a significant relationship between parenting and student career selection. The sample amounted to 96 students with a significance level of 5%, the r table value was 0.199. Therefore, r count < r table or 0.76 < 0.199 means that there is a relationship between parenting patterns and the independence of student career choices.